2019
DOI: 10.1093/ajh/hpz191
|View full text |Cite
|
Sign up to set email alerts
|

Bedtimes and Blood Pressure: A Prospective Cohort Study of Mexican Adolescents

Abstract: INTRODUCTION Hypertension affects up to 5% of children worldwide and predicts later cardiovascular morbidity. Associations of short sleep and hypertension have been frequently reported in adults but less consistently in children. This study aims to examine the role of late bedtimes, a marker of short sleep duration, and potentially misaligned circadian rhythms, on incident elevated blood pressure (BP) in a large cohort of Mexican children. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
3
8
3
2
Order By: Relevance
“…Many studies have explored the association between sleep duration and BP. A A participant with earlier bedtime on a weekday also had a higher risk of elevated BP (risk ratio = 1.96; 95% CI =1.27, 3.01) (24), which was similar compared with our research. The biological mechanism of the relationship between sleep patterns and BP has not been clear yet.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have explored the association between sleep duration and BP. A A participant with earlier bedtime on a weekday also had a higher risk of elevated BP (risk ratio = 1.96; 95% CI =1.27, 3.01) (24), which was similar compared with our research. The biological mechanism of the relationship between sleep patterns and BP has not been clear yet.…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary to our results, in a study by Yan et al [ 37 ], a later bedtime (after midnight) was associated with an increased prevalence of diabetes (OR 1.446; 95% CI 1.107–1.888]. A U-shaped relationship between the prevalence of hypertension and bedtime was observed by Jansen et al [ 38 ]. The risk of hypertension was almost two-fold higher in those participants who went to bed before 9 p.m., as well as after 11 p.m., in comparison to those, who went to bed between 9 p.m. and 11 p.m. (RR 1.96; 95% CI 1.27–3.01; RR1.87; 95% CI 1.09–2.21, respectively) [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A U-shaped relationship between the prevalence of hypertension and bedtime was observed by Jansen et al [ 38 ]. The risk of hypertension was almost two-fold higher in those participants who went to bed before 9 p.m., as well as after 11 p.m., in comparison to those, who went to bed between 9 p.m. and 11 p.m. (RR 1.96; 95% CI 1.27–3.01; RR1.87; 95% CI 1.09–2.21, respectively) [ 38 ]. Similarly, a U-shaped relationship between bedtime and health outcomes was observed in the global PURE study [ 8 ].…”
Section: Discussionmentioning
confidence: 78%
“…25 Jansen et al found that Mexican adolescents with a weekday bedtime later than 11pm had a 1·87 times higher risk of developing elevated BP than the participants with a bedtime between 9pm and 10pm, after accounting for sleep-related confounders. 26 In our study, however, the association between timing of sleep and CVD incidence remained robust even after additional adjustment for important CVD risk factors, such as hypertension, diabetes, BMI, and smoking.…”
Section: Discussioncontrasting
confidence: 62%